Bethlem myopathy: An autosomal dominant myopathy with flexion contractures, keloids, and follicular hyperkeratosis - Saroja, Aralikatte Onkarappa (Medknow Publications & Media Pvt Ltd, 2013)
Bethlem myopathy and Ullrich congenital muscular dystrophy form a spectrum of collagenopathies caused by genetic mutations encoding for any of the three subunits of collagen VI. Bethlem phenotype is relatively benign and is characterized by proximal dominant myopathy, keloids, contractures, distal hyperextensibility, and follicular hyperkeratosis. Three patients from a single family were diagnosed to have Bethlem myopathy based on European Neuromuscular Centre Bethlem Consortium criteria. Affected father and his both sons had slowly progressive proximal dominant weakness and recurrent falls from the first decade. Both children aged 18 and 20 years were ambulant at presentation. All had flexion contractures, keloids, and follicular hyperkeratosis without muscle hypertrophy. Creatinine kinase was mildly elevated and electromyography revealed myopathic features. Muscle imaging revealed severe involvement of glutei and vasti with “central shadow” in rectus femoris. Muscle biopsy in the father showed dystrophic changes with normal immmunostaining for collagen VI, sarcoglycans, and dysferlin.